“Percepción estética de la sonrisa según la exposición gingival de los estudiantes de estomatología de la Universidad Nacional de Trujillo, 2021” - Silva Otiniano, Rick Globert (2022)
The purpose of this study was to determine the esthetic perception of the smile according to the gingival exposure of stomatology students of the Universidad Nacional de Trujillo,2021.The sample consisted of a total of 127 students. Five photographs of the smile with different levels of gingival exposures (-2 mm, 0 mm, +2 mm, +4 mm, +6 mm) were used, taken from the study conducted by Luján33 entitled "Aesthetic perception of the smile in a group of dentists and patients according to gingival exposure" carried out in 2018. The perception of stomatology students was determined using a visual analog scale (VAS). The results showed that the stomatology students gave higher ratings to the smile photographs presenting a level of gingival exposure -2 mm and 0 mm, while the photograph that scored the lowest was the image with the smile presenting the highest level of gingival exposure (+6 mm).It is concluded that, the photograph with the smile presenting 2 mm of upper lip coverage over the upper central incisors (gingival exposure level -2 mm, Photograph 1) received the highest rating by the students. In addition, equality was rejected with a highly significant statistical difference when comparing the mean score of the ratings between all levels of gingival exposures.